Regulatory Framework, Contractual Structures, and Legal Challenges of Conventional and Sharia Equity Crowdfunding (ECS) for MSME Financing in Indonesia: Comparative Analysis with Malaysia - Mohd Zakhiri MD NOR; Nadiya Salsabila Noor; Irma Rachmawati Maruf (International Journal of Latin Notary, 2025)
This study examines the regulatory framework, contractual structures, and legal challenges of conventional and sharia equity crowdfunding as alternative financing mechanisms for Micro, Small, and Medium Enterprises in Indonesia, with comparative insights from Malaysia. The research employs a normative legal methodology analyzing primary legal instruments including Indonesian Finance Authority Regulation, and related regulations, supplemented by empirical literature examining crowdfunding implementation in both jurisdictions. The findings reveal that Indonesia operates a dual regulatory framework combining securities regulations with Islamic jurisprudential guidance, while Malaysia pioneered ECS licensing in 2015 with ongoing debates regarding Sharia governance depth. Conventional equity crowdfunding employs standard share subscription agreements under corporate law, whereas sharia equity crowdfunding utilizes Islamic contracts including musharakah, mudharabah, qardh hasan, and ijarah to ensure compliance with prohibitions against riba, gharar, and maysir. The study identifies three significant legal issues: regulatory gaps particularly concerning sharia share offering provisions and Sharia Supervisory Board responsibilities, cybercrime vulnerabilities affecting unregistered platforms comprising approximately ninety percent of sharia operators, and money laundering risks through electronic payment mechanisms. The research further demonstrates that religious investors significantly influence crowdfunding success, with Islamic campaigns attracting 37.1 percent higher funding based on empirical evidence from comparable markets. The study concludes that effective sharia crowdfunding development requires statutory-level legislation, enhanced Indonesian Finance Authority Regulation supervision of unregistered platforms, mandatory cybersecurity standards, comprehensive Sharia governance frameworks with separate review, audit and risk functions, and targeted financial literacy programs. These recommendations aim to bridge the gap between sharia principles and positive law while expanding MSME access to equity-based financing aligned with maqasid al-Shariah objectives.